Electrochemical In Situ Fabrication of Titanium Dioxide Nanotubes on a Titanium Wire as a Fiber Coating for Solid-Phase Microextraction of Polycyclic Aromatic Hydrocarbons - Mingguang Ma (MDPI AG, 2021)
A novel titanium dioxide nanotube (TiO2NTS) coated fiber for solid-phase microextraction (SPME) was prepared by in situ anodization of titanium wire in electrolyte containing ethylene glycol and ammonium fluoride (NH4F). The effects of different electrolyte solutions (NH4F and ethylene glycol) and oxidation voltages on the formation and size of TiO2NTs was studied. It was obtained from the experiment that TiO2NTs arrays were arranged with a wall thickness of 25 nm and the diameter of 100 nm pores in ethylene glycol and water (v/v, 1:1) containing NH4F of 0.5% (w/v) with a voltage of 20 V at 25 °C for 30 min. The TiO2NTs were used as solid-phase microextraction fiber coatings coupled with high-performance liquid chromatography (HPLC) in sensitive determination of polycyclic aromatic hydrocarbons (PAHs) in spiked real samples water. Under the optimized SPME conditions, the calibration curve has good linearity in the range of 0.20–500 μg·L−1, and the correlation coefficient (R2) is between 0.9980 and 0.9991. Relative standard deviations (RSDs) of 3.5–4.7% (n = 5) for single fiber repeatability and of 5.2% to 7.9% for fiber-to-fiber reproducibility (n = 3) was obtained. The limits of detection (LOD) (S/N = 3) and limits of quantification (LOQ) (S/N = 10) of PAHs were 0.03–0.05 µg·L−1 and 0.12–0.18 µg·L−1. The developed method was applied to the preconcentration and determination of trace PAHs in spiked real samples of water with good recoveries from 78.6% to 119% and RSDs from 4.3 to 8.9%, respectively.